Organic agriculture in Kenya and Uganda: study visit report - Walaga, Charles (Technical Centre for Agricultural and Rural Cooperation, 2005)
This report was produced following a study visit to Kenya and Uganda, 19–30 April 2004. The visit was sponsored by CTA and organised in collaboration with ORREDE and SACDEP–Kenya.